An Outbreak of non-sexually transmitted gonococcal conjunctivitis in Central Australia and the Kimberley region - Matters, Rex; Wong, Ignatius; Mak, Donna (Communicable Diseases Intelligence, 1998)
From 13 February to 27 June 1997, 447 cases of gonococcal conjunctivitis were identified by Communicable Disease and Public Health Centres and Community Clinics in the Northern Territory, Western Australia and South Australia. The outbreak involved Aboriginal communities predominantly in Central Australia and the Kimberley region in Western Australia. This was the first outbreak recorded in the Kimberley region. It is not yet known whether the Kimberley cases were part of the larger Central Australian outbreak or whether they represented a separate and unrelated outbreak. Environmental factors associated with this outbreak were similar to those seen in previous outbreaks. Control measures were based on early recognition and treatment of index cases and identifying and treating contacts. Until sexually transmitted Neisseria gonorrhoeae is controlled in communities gonococcal conjunctivitis is likely to appear again. The role of oropharyngeal carriage of N. gonorrhoeae needs to be evaluated further. Commun Dis Intell 1998;22:52-58.